Overview of the actions to combat bacterial resistance in large hospitals - Mariana Sanches de Mello; Adriana Cristina Oliveira (Universidade de São Paulo, 2021)
Objective: to analyze, in the clinical practice of large hospitals, how the adoption of measures to prevent and control the spread of bacterial resistance has occurred, and to propose a score for the institutions' adherence. Method: a cross-sectional study carried out in 30 large hospitals of Minas Gerais, from February 2018 to April 2019, after approval by the Ethics and Research Committee. Interviews were conducted with hospital managers, with Hospital Infection Control Services coordinators, and with the care coordinators of the Inpatient Units and Intensive Care Center. In addition, observations were made of the adoption of preventive measures by the multidisciplinary team in the care units. Results: in the 30 participating hospitals, 93.3% (N=28) had protocols for prophylactic antibiotics, and 86.7% (N=26) performed their audit, 86.7% (N=26) for therapeutic antibiotics and 83.3% (N=25) their audit; 93.3% (N=56) used gloves and cloaks for patients in contact precautions, and 78.3% (N=47) of the professionals were unaware of or answered incompletely on the five moments for hand hygiene. In the score to identify the adoption of measures to control bacterial resistance, 83.3% (N=25) of the hospitals were classified as partially compliant, 13.3% (N=04) as deficient, and 3.4% (N=01) as non-adoption. Conclusion: it was found that the recommended measures to contain bacterial resistance are not consolidated in the clinical practice of the hospitals.